Respuesta :

Answer:

C

Step-by-step explanation:

Given

f(x) = x² + x + 1

To obtain the function in vertex form use the method of completing the square.

Add/ subtract ( half the coefficient of the x- term )² to x² + x

f(x) = x² + 2([tex]\frac{1}{2}[/tex] )x + [tex]\frac{1}{4}[/tex] - [tex]\frac{1}{4}[/tex] + 1

     = (x + [tex]\frac{1}{2}[/tex] )² + [tex]\frac{3}{4}[/tex] → C

Answer:

C

Step-by-step explanation:

x² + x + 1

x² + 2(x)(½) + (½)² - (½)² + 1

(x + ½)² - ¼ + 1

(x + ½)² + ¾